Oral storytelling and national kinship: Reflections on the oral narrative performance in the Kenya Schools and Colleges Drama Festivals - Opondo, Rose A. (Tydskrif vir Letterkunde, 2014)
The story, in the form of the oral narrative, has always been a communalizing genre in the traditional African setting. It then functioned as a tool that brings together not only the artist and the particular audience, but also the entire community within which the performances are derived and performed. However, postcolonial, modern and global situations have greatly impacted on the traditional kinship structures in Africa and kinship fostering tools like the African oral narrative have not been spared. The introduction of the oral storytelling onto the proscenium stage in the Kenya Schools and Colleges Drama Festivals (KSCDF) has contributed to perpetuate the performance of this genre to significant degrees. This move has not only recalled attention to oral narratives, but also has revolutionized the performance and functional aspects of oral storytelling. Various aspects of the oral narrative genre have changed, from the multi-ethnic audience to the elaborate narrative structures and the varying orientationsÂ  of the oral artists in KSCDF. The dramatic elements of the narrative have also been enhanced to justify its inclusion within the wider dramatic genre. This article investigates the structural and thematic reorientations of the contemporary Kenyan oral narrative and how it influences the reorientations of kinship in a postcolonial reality characterized by heterogeneous consumer audience and the need for national commonality. The aim is to understand the reorientations of oral storytelling and its scripted machinations of multi-ethnicity woven into the narrative as part of its contemporarily requisite features; the question is whether or not these reorientations enable the ideological adoption of some form of kinship across the diverse ethnic groups in Kenya.